The Early Microleakage of a Fflowable Composite in Class V Restorations - Ammar Kh Al–Nori (Al-Rafidain Dental Journal, 2009)
Aims: To evaluate microleakage in Class V restorations, which were restored with flowable compositescompared to hybrid composite and to evaluate the difference of microleakage between occlusaland gingival margins. Materials and methods: Forty five non–carious upper premolar teeth were randomlydistributed into 3 groups of 15 teeth each. Class V preparations were made in the buccal surfacesof each tooth and restored by the use of two flowable composites (Tetric and Megafill) and thethird group with hybrid composite (Tetric Ceram). The specimens were stored in distilled water at 37°C for 24 hours. The specimens were then thermocycled manually for 100 times between 5 + 2 °C and55 + 2 °C. All restored teeth were immersed in 0.2% methylene blue dye for 24 hours and sectionedbuccolingually with a finishing diamond wheel. Dye penetration was scored by use of a stereoscopicmicroscope under magnification of ×20. Results: The flowable composites had a significant effect onreducing the microleakage at gingival margin (p= 0.01). The type of material had no significant effectat occlusal margin (p= 0.454). The occlusal margin had significantly lower microleakage than gingivalmargin (p= 0.001). Conclusions: The flowable composites can reduce the microleakage at gingivalmargins, but non of the restorative materials completely sealed the tooth restoration interface.